RETRACTED: Endothelial-Monocyte Activating Polypeptide II Suppresses the In Vitro Glioblastoma-Induced Angiogenesis by Inducing Autophagy - Li, Zhiqing; Ma, Jun; Liu, Libo; Liu, Xiaobai; Wang, Ping; Liu, Yunhui; Li, Zhen; Zheng, Jian; Chen, Jiajia; Tao, Wei; Xue, Yixue (Frontiers in Molecular Neuroscience, 2017)
The obstacle in delivering therapeutics to glioblastoma (GBM) is tumor-induced angiogenesis which leads to the formation of abnormal vessels and a dysfunctional blood-tumor barrier (BTB). Here, we elucidated the effect of endothelial-monocyte activating polypeptide II (EMAP II) on the GBM-induced angiogenesis as well as its potential mechanisms. Our results proved that EMAP II inhibited the viability, mitochondrial membrane potential (MMP), migration and tube formation of GBM-induced endothelial cells (GECs) by inducing cell autophagy, demonstrated by cell viability assay, JC-1 staining assay, transwell assay and tube formation assay, respectively. Cell autophagy was induced by EMAP II through the observation of autophagic vacuoles formation and the up-regulation of microtubule-associated protein-1 light chain-3 (LC3)-II and p62/SQSTM1 expression, demonstrated by transmission electron microscopy (TEM) analysis, immunofluorescence assay and Western blot assay. The activity of PI3K/AKT/mTOR signal pathway could be inhibited by the EMAP II treatment. Furthermore, unfolded protein response (UPR)-related proteins (GRP78, eIF2α and CHOP) were up-regulated by EMAP II, which suggest that GECs exposed to EMAP II experienced endoplasmic reticulum (ER) stress. Further, mechanistic investigations found that EMAP II reduced the miR-96 expression which could directly target the 3′-UTR of these UPR-related proteins, and over-expression of miR-96 inhibited LC3 and p62/SQSTM1 expression by down-regulating these UPR-related proteins in GECs. Moreover, the combination of EMAP II with miR-96 inhibitor showed the inhibitory effect on the viability, migration and in vitro tube formation of GECs, which are critical for angiogenesis. Taken together, we have demonstrated the fact that EMAP II resulted in the decreased GBM-induced angiogenesis by inducing autophagy, which might contribute to establishing potential strategies for human GBM treatment.